Bottom of Pyramid Marketing: A Bibliometric Analysis and Future Directions - Brahmane, Prashant (International Review of Management and Marketing, 2025)
This study aims to examine the trends and characteristics of The Bottom of pyramid (BoP) marketing research published from 2014 to 2024 to identify the track of the research area, provide information about major contributors, and suggest future direction for research. This study used the Scopus database, searched for relevant articles using the keyword “Bottom of pyramid marketing,” and compiled the results using different bibliometric analysis software. A total of 219 articles were identified, but only 83 were included in this study. This study observed a volatile trend in publishing articles in this research area. The journal Emerald Emerging Markets Case Studies published the most articles. At the same time, the most cited was the Journal of Retailing and Consumer Service. Important keywords were Bottom of the pyramid, marketing, Emerging market, India, and Poverty. Many countries have published research in this area. This study uses TCM (Theory, Context, and Methods) framework for identifying limitations, and future recommendations. It also suggests developing a theoretical framework and practical applications in BoP marketing.